Completeness and Feasibility Analysis of Skateparks in Bandung City: A Case Study on Sports Facilities - Afendy, Fauzy Nugraha; Septiana, Rama Adha; Karisman, Vicki Ahmad; Buntoro, Josep Dharmadi (STKIP Paasundan Press, 2025)
This study aims to analyze the completeness and feasibility of three skateparks in Bandung City, namely Buqiet, Pasoepati, and Taman Pramuka Skatepark. Data were obtained through interviews, field observations, and documentation involving the skateboarding community and skatepark management. The results indicate that Buqiet Skatepark has complete and well-maintained facilities, as well as adequate safety systems. Meanwhile, Pasoepati and Taman Pramuka Skatepark have acceptable facilities, but they are less complete, with several deficiencies in obstacles and a lack of information boards and safety signs. All three skateparks are in good condition; however, improvements are needed in terms of facility diversity and safety aspects. This study recommends that the Bandung City government enhance the standards of completeness and safety of skatepark facilities and involve the local community in the planning and management of the skateparks.